2021
DOI: 10.1097/fjc.0000000000001004
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Novel Agents and Clinical Considerations in Patients With ATTR Cardiac Amyloidosis

Abstract: Transthyretin (ATTR) amyloidosis is a multisystem disease caused by organ deposition of amyloid fibrils derived from the misfolded transthyretin (TTR) protein. The purpose of this article is to provide an overview of current treatment regimens and summarize important considerations for each agent. A literature search was performed with the PubMed database for articles published through October 2020. Search criteria included therapies available on the market and investigational therapies used for ATTR amyloidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…2 Clinical trials are also ongoing for investigational therapies for ATTR-CM, including the transthyretin stabilizer acoramidis, which may also prove to be beneficial against this progressive multisystem disease. 10,11 The growing preference for 99m Tc-PYP bone scintigraphy observed in this study is consistent with recent advances in diagnostic strategies 1,9 and expert consensus recommendations. 4−6 Increased recognition of the importance of this diagnostic tool has been accompanied by a raised awareness of 'red flag' sign/symptom patterns, such as heart failure with preserved ejection fraction, carpal tunnel syndrome, lumbar spinal stenosis, and spontaneous biceps tendon rupture, that may be early manifestations of ATTR-CM.…”
Section: Discussionsupporting
confidence: 86%
“…2 Clinical trials are also ongoing for investigational therapies for ATTR-CM, including the transthyretin stabilizer acoramidis, which may also prove to be beneficial against this progressive multisystem disease. 10,11 The growing preference for 99m Tc-PYP bone scintigraphy observed in this study is consistent with recent advances in diagnostic strategies 1,9 and expert consensus recommendations. 4−6 Increased recognition of the importance of this diagnostic tool has been accompanied by a raised awareness of 'red flag' sign/symptom patterns, such as heart failure with preserved ejection fraction, carpal tunnel syndrome, lumbar spinal stenosis, and spontaneous biceps tendon rupture, that may be early manifestations of ATTR-CM.…”
Section: Discussionsupporting
confidence: 86%
“…Monoclonal antibodies developed against serum amyloid P (SAP) (constituent that contributes to aggregate stability) and TTR (including PRX004) have disclosed mixed results. While initial murine and human studies of anti-SAP led to clearance of amyloid tissue deposits, ongoing clinical trials have been suspended 90–92. A recent small phase I trial of PRX004 demonstrated safety and tolerability of anti-TTR treatment while reducing progression of neuropathy and cardiac disease (https://ir.prothena.com/static-files/ee65ab75-2e8b-4eae-989b-3de7c7bd9149).…”
Section: Ttr Fibril Removalmentioning
confidence: 99%
“…While initial murine and human studies of anti-SAP led to clearance of amyloid tissue deposits, ongoing clinical trials have been suspended. 90–92 A recent small phase I trial of PRX004 demonstrated safety and tolerability of anti-TTR treatment while reducing progression of neuropathy and cardiac disease ( https://ir.prothena.com/static-files/ee65ab75-2e8b-4eae-989b-3de7c7bd9149 ). Phase II studies of anti-TTR monoclonal antibodies are ongoing.…”
Section: Ttr Fibril Removalmentioning
confidence: 99%
“…There are also clinical trials with the use of a specific monoclonal antibody PRX 004 affecting amyloid degradation. 61 In extreme cases, heart and liver transplants are performed.…”
Section: Therapeutic Proceduresmentioning
confidence: 99%